Adding unregulated nursing support workers to ward staffing: Exploration of a natural experiment. Issue 19 (13th August 2018) - Duffield, Christine; Roche, Michael; Twigg, Di; Williams, Anne; Rowbotham, Samantha; Clarke, Sean
Abstract: Aims and objectives: To explore the impact of an initiative to add unregulated nursing support workers to wards in acute care hospitals. Background: Adding nursing support workers to existing nurse staffing may be one solution to reduce nursing workloads and improve outcomes. However, the effects of this addition on nurse, patient and system outcomes are not well documented. In one state of Australia, a trial deployment of nursing support workers to wards across the public health system provided opportunity for the exploration of their impact in a natural, real‐world, environment. Design: Cross‐sectional study. Methods: A sample of five wards where nursing support workers had been added matched to a group of five wards where there were no nursing support workers. Data were collected via patient survey ( n = 141) and nurse survey ( n = 154). Analysis was comparative with regression models constructed for the different ward types. Results: Nursing leadership, staffing and resources, and nurse experience were linked to outcomes on both ward types. Instability was a significant predictor of reduced quality of care and increased turnover intention on wards where support workers were added. Conclusion: Adding nursing support workers to ward staffing did not lead to improvements in patient care. Findings suggest that staffing a nursing ward is a complex activity and that a simple approach to staffing is unlikely to be successful. Future research should explore the process of implementation and the conditions under which this strategy is likely to be successful. Relevance to clinical practice: Ward‐level factors are key in making appropriate staffing and skill mix choices to limit instability and to consequently avoid negative patient, staff and system outcomes. Consideration of the ward context, alongside effective delegation processes and integration into the care team are imperative when adding nursing support workers.